2019
DOI: 10.3390/ma12091529
|View full text |Cite
|
Sign up to set email alerts
|

N-Type Bismuth Telluride Nanocomposite Materials Optimization for Thermoelectric Generators in Wearable Applications

Abstract: Thermoelectric materials could play a crucial role in the future of wearable electronic devices. They can continuously generate electricity from body heat. For efficient operation in wearable systems, in addition to a high thermoelectric figure of merit, zT, the thermoelectric material must have low thermal conductivity and a high Seebeck coefficient. In this study, we successfully synthesized high-performance nanocomposites of n-type Bi2Te2.7Se0.3, optimized especially for body heat harvesting and power gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…The authors revealed that at 300K, the highest value of 0.14 was achieved by the synthesized sample at 1Gpa pressure. Nozariasbmarz et al [50] tried to improve the TE properties of bulk nanostructured n-type Bi2Te2.7Se0.3 materials using different techniques, including dopant addition, tellurium vacancies, glass inclusion, spark plasma sintering time and temperature, microwave processing, and subsequent annealing. The experiments were focused on optimizing the materials' properties concerning wearable TEGs.…”
Section: P Type Inorganic Te Materialsmentioning
confidence: 99%
“…The authors revealed that at 300K, the highest value of 0.14 was achieved by the synthesized sample at 1Gpa pressure. Nozariasbmarz et al [50] tried to improve the TE properties of bulk nanostructured n-type Bi2Te2.7Se0.3 materials using different techniques, including dopant addition, tellurium vacancies, glass inclusion, spark plasma sintering time and temperature, microwave processing, and subsequent annealing. The experiments were focused on optimizing the materials' properties concerning wearable TEGs.…”
Section: P Type Inorganic Te Materialsmentioning
confidence: 99%
“…The (zT) peak of Type (I)-n and Type (II)-n is 0.92 and 0.9, respectively. In Type (II)-n, zT~0.9 is maintained in a broad temperature range from 50 C to -n has lower thermal conductivity and higher Seebeck coefficient and zT at room temperature, which makes this material appropriate for applications that require large contact resistance between TE and heat source/sink at room temperature such as wearable electronics (Nozariasbmarz et al, 2019a(Nozariasbmarz et al, , 2019b2020a, 2020b. However, comparatively Type (I)-n is not the best candidate for power generation at high temperature due to its zT degradation.…”
Section: Open Accessmentioning
confidence: 99%
“…These are often connected thermally in parallel and electrically in series, demonstrating the efficiency and enhancing diversity for applications. In this study, thin films of Antimony (Sb) were chosen as an p-type material, and Selenium (Se) was chosen as a n-type material [12,13]. Figure 3 represents the X-ray diffraction (XRD) patterns of BiTeSb and BiTeSe thin films on various substrates at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In general, commercial thermoelectric devices are produced from sintered bulk materials. However, these bulk materials have a low figure of merit (ZT) due to both their electrical conductivity and low Seebeck coefficients [2,9,13]. To increase thermoelectric properties, low-dimensional interactions are used to boost the density of states (DOS) in the vicinity of the Fermi level, enhancing phonon scattering on nanostructured materials and giving a lead to increase charge carrier mobility [10] and thin film nanotechnology allows for the probability of decorating the devices to micro-or nanodimensions and for easy coordination with the standard applications with different substrate options.…”
Section: Introductionmentioning
confidence: 99%